A review of current concepts in the management of proximal humerus fractures. (July 2015) - Handford, Charles; Nathoo, Shakira; Porter, Keith; Kalogrianitis, Socrates
Fracture of the proximal humerus is a common orthopaedic injury and is likely to increase in incidence. This fracture type is associated with a wide variety in fracture morphology and as a direct result there are many treatment options available. It is often not clear what treatment modality should be utilised. This article reviews the current literature on proximal humerus fractures offering evidence for care pathways and management strategies from presentation to rehabilitation.